MEN’S FASHION IN THE CONTEXT OF ECO-SUSTAINABLE DESIGN PRODUCT CONSUMPTION PRACTICES (PROJECT EXPERIENCE) - Hurdina, Vladyslava; Yermakova, Tetiana; Tokar, Maryna (Theory and practice of design, 2024)
Modern men’s fashion is a unique branch of designer creativity and is no less popular than women’s fashion. But so far it is poorly represented in the scientific literature and needs more detailed research. The article aims to identify modern methods in the field of ecological design, which can be applied in the design of men’s clothing, as well as to explore the interaction between men’s fashion trends and ecological design concepts. Purpose. The article analyzes the scientific literature on ecological design in general and eco-design of clothes in particular. Methodology. The main challenges and methods of ecological clothing design and their relevance in men’s fashion are traced via the classification method. Using the method of visual comparison, fashion trends for men’s clothing for the spring of 2024 were analyzed and those that can be used in eco-oriented design practices were identified. With the help of the experimental method, a project experience of working with students was carried out in the framework of ecological design of men’s clothing, focusing on fashion trends and explained in the article. Results. The article found that the design of men’s eco-friendly clothing appeals to the same methods as women’s clothing: upcycling, recycling, use of natural materials, environmental advocacy, etc. However, ecological approaches are much less common in the design and production of men’s clothing, as well as in fashion shows at fashion weeks, than in women’s clothing. Scientific novelty. The topic of ecological design of men’s clothing is currently less developed than that of women’s clothing. This applies to both design practices and research. The article outlines fashion trends in which the use of ecological design methods would be appropriate. Practical significance. The results of the study and the principles of ecological design can be implemented in students’ project assignments. It is important to educate future fashion designers about environmental awareness.